THE INFLUENCE OF COOPERATIVE LEARNING TECHNIQUE AND READING INTEREST TOWARDS THE EIGHTH GRADE STUDENTS’ READING COMPREHENSION ON RECOUNT TEXT OF SMPN 48 PALEMBANG - Diana Sari (ELTE Journal (English Languange Teaching and Education), 2019)
AbstractThis research is concerned with the influence of cooperative learning technique and reading interest towards the eight grade students’ reading comprehension on recount text of SMPN 48 Palembang. In this study 60 students of eighth grade students of SMPN 48 in the academic year 2017/2018 were chosen as samples by means of two stage random sampling. This study applied factorial research design. The data were collected by using questionnaires and t-test. The data were analyzed by using Paired Sample t-test, Independent Sample t-test and Two Ways Anova. The results showed that, first, there was a significant difference in reading comprehension the students who have high reading interest and those who have low reading interest taught using cooperative learning technique of SMPN 48 Palembang. Second, there was not any significant difference in reading comprehension the students who have high reading interest and those who have low reading interest taught by traditional teaching method of SMPN 48 Palembang. Third, there was a significant difference in reading comprehension the students who have high reading interest and those who have low reading interest taught using cooperative learning technique and traditional teaching method of SMPN 48 Palembang. Lastly, there were not any significant interaction effects of cooperative learning technique and reading interest towards the students’ reading comprehension of SMPN 48 Palembang. Conclusion suggests that there were significant influences of cooperative learning technique and reading interest the eighth grade students’ reading comprehension on recount text of SMPN 48 Palembang.Keywords: Cooperative Learning Technique, Traditional Teaching Method, Reading Interest, Reading Comprehension.